2023
DOI: 10.3390/app13148380
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physiological, Physical, and Tactical Responses in Small-Sided Games in Women’s Soccer: The Effect of Numerical Superiority

Danillo Silveira Trombiero,
Gibson Moreira Praça,
Eduardo de Paula Amorim Borges
et al.

Abstract: Small-sided and conditioned games (SSGs) are pedagogical tools that help in soccer training, being used to solve tactical problems with the specific demands of the game. In this context, this study aimed to compare physical, physiological, and tactical responses in elite women’s soccer in SSGs with numerical equality (3-a-side) and superiority (3-a-side + 1) in the offensive phase. The sample consisted of 16 female athletes participating in official national competitions. Two consecutive days of data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Studies on match analysis in sports currently indicate a correlation between performance and game location [11,12], player experience [13,14], type of game played [13,15] game rules [15,16], offensive and defensive phases [4,17], team level [11,18], and other aspects inherent to the game context. Furthermore, it is observed that the analysis of tactical behaviors, for the most part, results from the interpretation of general metrics [19][20][21], examining the team's tactical behaviors that specify success or failure in the match [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on match analysis in sports currently indicate a correlation between performance and game location [11,12], player experience [13,14], type of game played [13,15] game rules [15,16], offensive and defensive phases [4,17], team level [11,18], and other aspects inherent to the game context. Furthermore, it is observed that the analysis of tactical behaviors, for the most part, results from the interpretation of general metrics [19][20][21], examining the team's tactical behaviors that specify success or failure in the match [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Football is a complex and high physically demanding sport [1][2][3]. Analyses of physical demands in football are usually conducted through the quantification of physical performance, such as total distance, distance covered in different speed zones, and acceleration frequencies [4][5][6].…”
Section: Introductionmentioning
confidence: 99%